THE EFFECT OF THE HYDROCHLORIC ACID CONCENTRATION TO THE CHARACTERISTICS OF BLACK SEA CUCUMBER (Holothuria edulis) CHITIN - Vran Orlando Josua; Edison '; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aims to determine the physico-chemical characteristics of black sea cucumber ( Holothuria edulis) chitin, get the best hydrochloric acid concentration in demineralization process from crude chitin to chitin, and to determine the highest deacetylation degree of black sea cucumber chitin. This research was conducted in two phases. The first was preparation and the second was drying, sieving, and manufacturing the chitin. The result showed that the different concentration of HCl did not effect significantly to the water content and ash content of black sea cucumber chitin. Meanwhile, the highest deacetylation degree was obtained by the using of HCl at the consentration of 1 N, followed by the concentration 0,5 N then 1,5 N.Keywords : ash content, black sea cucumber, deacetylation degree, water content.